Abnormal Right Ventricular Myocardial Performance Index Is Not Associated With Outcomes in Invasively Ventilated Intensive Care Unit Patients Without Acute Respiratory Distress Syndrome—Post hoc Analysis of Two RCTs - Pierrakos C. (2023)
Background: The objective of the study was to determine the association between right ventricular (RV) myocardial performance index (MPI) and successful liberation from the ventilator and death within 28 days. Methods: Post hoc analysis of 2 ventilation studies in invasively ventilated patients not having ARDS. RV-MPI was collected through transthoracic echocardiography within 24–48 h from the start of invasive ventilation according to the study protocols. RV-MPI ≤ 0.54 was considered normal. The primary endpoint was successful liberation from the ventilator < 28 days; the secondary endpoint was 28-day mortality. Results: A total of 81 patients underwent transthoracic echocardiography at median 30 (24–42) h after the start of ventilation—in 73 (90%) patients, the RV-MPI could be collected. A total of 56 (77%) patients were successfully liberated from the ventilator < 28 days; A total of 22 (30%) patients had died before or at day 28. A total of 18 (25%) patients had an abnormal RV-MPI. RV-MPI was neither associated with successful liberation from the ventilator within 28 days [HR, 2.2 (95% CI 0.47–10.6); p = 0.31] nor with 28-day mortality [HR, 1.56 (95% CI 0.07–34.27); p = 0.7]. Conclusion: In invasively ventilated critically ill patients without ARDS, an abnormal RV-MPI indicative of RV dysfunction was not associated with time to liberation from invasive ventilation.